The problem of Christian identities in Ephesians: Inspiration from the work of Nils Alstrup Dahl. (2nd January 2016) - MacDonald, Margaret Y.
Abstract : The article examines the impact of the work of Nils Alstrup Dahl on contemporary New Testament scholarship about early Christian identities. The focus is specifically on the many complex questions related to identity in Ephesians, which include the nature of the document itself. The article draws upon a social constructionist approach in analysing the text, with a particular interest in the use of the language of Israel, emphasis on concepts of citizenship, and concentration upon the household and family life.